Boosting bike-commuting through active co-design: Artikel - Cooper, Christina (Proceedings from the Annual Transport Conference at Aalborg University, 2024)
In Kolding, the Mobility Plan 2023-2025 aims to lower the use of cars within a 5 km city centre range from 52% to 34% and similarly for the 10 km range. As more bicycle paths and recreational pedestrian corridors are not enough to ensure a significant reduction of shorter car trips, much of the reduction needs to come from citizen’s behaviour change.